Bronchoscopic Assessment of Radiologically Detected Lung Lesion - Chowdhury, Md Monjurul Kader; Biswas, Palash Kumar; Sarker, Partha Sarathi; Rahman, Md Saidur; Chowdhury, Tanzina Begum; Rahman, Md Masudur; Kalam Azad, Khan Abul (Journal of Medicine, 2023)
Background: Radiologically detected lung lesions are very common in regular clinical practice. It is very important to diagnose radiologically detected lung lesions early. Flexible fiber-optic bronchoscopy is an excellent minimally invasive and safe investigation for early diagnosis of lung diseases. Methods: Data were collected using a semi-structured questionnaire from the patients who had lesion on chest x-ray that were not in the peripheral part and advised for bronchoscopy. Patients were followed up after getting their histopathology. Statistical analysis using SPSS16.0 was carried out thereafter. Results: Mean age of the respondents was 56.8 years with age ranging from 25 to 85 years. 82% of the patients were male. Male-female ratio was 4.5:1. Endobronchial growth was found in maximum 46% patients during bronchoscopy, followed by 22% showing inflammatory lesion. In 20% of the patients, bronchoscopy findings showed normal findings and 12% patients showed inconclusive results. In subsequent biopsy and histopathology, maximum 55.88% showed non-neoplastic lesion. Among the non-neoplastic lesions 26.47% showed non-specific inflammation.20.58% showed tuberculosis, 5.88% showed sarcoidosis and 2.94% showed aspergilloma. 35.29% cases showed neoplastic lesion, 2.94% showed inconclusive results, 2.94% showed normal results and 2.94% showed inadequate sample. 58.33% cases were squamous cell carcinoma, 25% cases were adenocarcinoma, 8.33% showed small cell carcinoma and 8.33% showed mixed cell type of carcinoma. Conclusion: Fiberoptic bronchoscopy can be successfully employed for the diagnosis of lung diseases, including malignancies and granulomatous lesions.It is extremely useful in finding specific etiologies of various lung diseases. J MEDICINE 2023; 24(2): 106-111